The Mission [videorecording] - Bolt, Robert; Ghia, Fernando; Joffe, Robert; Puttnam, David; Warner Bros. ([Burbank, Calif.] Warner Home Video, 1986)
Based on historical events that occurred around the borderlands of Argentina, Paraguay and Brazil in the year 1750, the drama concerns two men, a priest and a soldier, who unite to shield a South American Indian tribe from brutal subjugation by 18th century colonial empires.
Director of photography, Chris Menges ; editor, Jim Clark ; music composed, orchestrated and conducted by Enno Monicone.
Robert De Niro, Jeremy Irons.
Keywords: Feature films; Historical films